Spare the rod, spoil the child: Bullying during medical internship in three Peruvian hospitals - Achata-Espinoza, Miguel (2017)
Bullying has traditionally been considered normal during health professional training. However, it is now recognized as harmful to both academic traiwning and mental and emotional health, with negative consequences such as low career satisfaction, depression, burnout syndrome, and post-traumatic stress symptoms. The hierarchy observed in the different stages of the medical career facilitates power abuse and makes medical students vulnerable. Likewise, frequently undervaluing abuse leads to less willingness to report bullying cases, and in the continuity of this behavior over time. During medical internships, students are also considered as workers, which increases the chances of being bullied; in addition, the training environment differs from what they experienced early in their career.